Identification of Proteins Associated with the Formation of Oral Biofilms - Pablo Alejandro Millones-Gómez; Reyma Evelyn Bacilio Amaranto; Dora Jesús Maurtua Torres; Roger Damaso Calla-Poma; Margarita F. Requena-Mendizabal; María Isabel Alvino-Vales; Rubén Calla-Poma (Association of Support to Oral Health Research (APESB), 2021)
Objective: To identify proteins associated with the formation of Streptococcus gordonii and Fusobacterium nucleatum biofilms. Material and Methods: Biofilms composed of two bacterial species, S. gordonii and F. nucleatum, were cultured for 1, 4, 7, and 10 days. The presence of both species was confirmed via amplification of the srtA and radD genes using real-time PCR. The concentrations of proteins associated with the biofilms and individual species were quantified using Western blotting. Results: The protein profiles of S. gordonii and F. nucleatum from individual cultures determined using one-dimensional electrophoresis revealed proteins found in S. gordonii and in F. nucleatum. Ct and reciprocal Ct values were determined for the exposed S. gordonii and F. nucleatum biofilms. Glyceraldehyde 3-phosphate dehydrogenase (GAPDH) protein was detected in biofilms and F. nucleatum, whereas HSP40 protein was present only in biofilms after 7 and 10 days of formation. Conclusion: HSP40 was detected only in the formed biofilms; thus, HSP40 is an essential proteins for adhesion.